Characterization and photoluminescence of Lu_2O_3-Eu~（3＋） nano-phosphor prepared by modified solution combustion method - 王林生 刘素琴 黄可龙 叶信宇 杨幼明 周智 (Journal of rare earths, 2011)
Nanoscale Lu2O3：Eu3＋ phosphor was prepared by a modified solution combustion method using urea and acrylamide monomer.The particle sizes and photoluminescent properties of nano-phosphor were closely related to the molar ratio of urea-to-RE nitrates and acrylamide monomer-to-RE nitrates.The as-prepared samples with the sizes of 9.6-11.6 nm were characterized by X-ray diffraction,scanning electron microscopy,transmission electron microscopy and energy dispersive spectrometer.Lu2O3：Eu3＋ nano-phosphor that depicted high photoluminescence in the size around 10 nm was reported.Compared with the sample prepared by solid state reaction,the photoluminescence of sample was increased sufficiently to be 45.1%.The emission spectra of the samples presented the typical emission from 5D0 level to 7FJ（J=0,1,2,3,4） level of the Eu3＋ ion.